KARAKTER FAIR PLAY DALAM OLAHRAGA BOLA VOLI : PERSPEKTIF ATLET, PELATIH, DAN WASIT DI KOTA JAMBI - Iqlima Puti Andini; Reza Hadinata; Bangkit Yudho Prabowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the city of Jambi, there are numerous futsal tournaments held, particularly among students. State High School 11 in Jambi City, one of the teams participating in city-wide and provincial student tournaments, often faces inadequate support for injured athletes during matches, as there are no first aid kits or ice available for immediate treatment when players sustain injuries during practice or games. The objective of this study is to determine the level of understanding among the futsal extracurricular players at State High School 11 in Jambi City regarding early injury management using the RICE method. This is a descriptive study employing a quantitative approach. The sample used in this study consists of all 21 futsal extracurricular players at State High School 11 in Jambi City. The results obtained for the “Interpretation” indicator were 78%, meaning that overall, the level of understanding among the futsal extracurricular players at SMA N 11 Kota Jambi regarding early injury management using the RICE method, specifically for the “Interpretation” indicator, falls into the “good” category. Consequently, 22% of the students indicated they lacked understanding of early injury management. For the “Interpretation” indicator, a score of 76% was obtained, meaning that overall, the level of understanding among the futsal extracurricular players at SMA N 11 in Jambi City regarding early injury management using the RICE method falls into the “good” category; consequently, 24% of the students who responded indicated they lacked understanding of early injury management. For the Extrapolation Indicator, a score of 80% was obtained, meaning that overall, the level of understanding among the extracurricular futsal players at SMA N 11 Kota Jambi regarding early injury management using the RICE method falls into the “good” category; consequently, 20% of the students indicated they lacked understanding of early injury management. The conclusion of this study is that the Level of Understanding of Extracurricular Futsal Players at SMA N 11 Jambi City Regarding Early Injury Management Using the RICE Method falls into the “good” category with a percentage of 78%; the ‘Interpreting’ indicator falls into the “good” category with a percentage of 78%; the “Interpreting” indicator falls into the “good” category with a percentage of 76%, and the ‘Extrapolating’ indicator falls into the “good” category with a percentage of 80%.